NANOTECHNOLOGY AND AGRICULTURAL NANOFERTILIZERS (REVIEW ARTICLE) - Abobatta Waleed (Mesopotamia Journal of Agriculture)
Due to the adverse effects of continuous climate change on agricultural production and the increased food demand globally, there is an urgent need to use new strategies to improve agricultural production in a sustainable manner and maximize the efficiency of available natural resources. Nanotechnology represents a key tool for the advancement of agriculture with biotechnology, which could be a new management practice that increases the efficiency of agricultural resources and reduces the excessive use of agrochemicals, which pose a serious threat to the environmental system, while also producing healthy and safe food, reducing production costs, and preserving the environment. Nanotechnology includes several tools, including nanomaterials such as nano fertilizers and nano pesticides, in addition to nano-packaging materials, nano-devices such as sensors, nano-robots, and nano-barcode devices. There are three main methods used in the manufacture of nanomaterials, including chemical, physical, and biological routes, the chemical route is the most widespread so far. Nanotechnology is one of the important tools that have a profound impact on agricultural practices to enhance growth and increase crop yield. Nanoparticles, due to their unique properties, provide many benefits, whether in improving the growth and productivity of different crops, reducing the quantities of fertilizers used, reducing the negative effects of climate change on production, or diagnosing diseases in their early stages. Nano fertilizers could be applied as a foliar or soil application, so they are considered one of the most important applications in agriculture due to their numerous benefits.